Euro Area Policies : Financial Sector Assessment Program-Technical Note-Systemic Risk Analysis. (IMF Staff Country Reports; Country Report ;, 2018)
This technical note consists of five chapters focusing on various aspects of systemic risk analysis across the euro area financial system. The chapters cover bank profitability, balance sheet- and market-based interconnected analysis, contingent claims analysis, and a brief discussion of data gaps in the nonbank, non-insurance (NBNI) financial sector. The ongoing economic recovery will support euro area bank profitability in general, but it is unlikely to resolve the structural challenges faced by the least profitable banks despite some recent improvements. This is important because persistently weak bank profitability is a systemic financial stability concern. Empirical analysis of 109 major euro area banks over 2007-2016 reveals that real GDP growth and the NPL ratio are the most reliable determinants of profitability, after accounting for other factors. Although higher growth would raise profits, a large swath of banks with the weakest profitability would most likely continue to struggle even with a robust recovery. Therefore, banks should take advantage of the current upswing by resolutely addressing their NPL stocks-such a strategy holds the most promise for weak banks' profitability prospects.